Effect of Velocity Index on Grain Size of Friction Stir Processed Al-Zn-Mg-Cu Alloy. (2016) - Patel, Vivek V.; Badheka, Vishvesh J.; Kumar, Abhishek
Abstract: Friction stir processing is an effective tool for microstructure modification by refining the microstructure in aluminum alloys. In this study, the effect of velocity index (tool rotation speed/traverse speed) on resulting grain microstructure of friction stir processed high strength Al-Zn-Mg-Cu alloy is reported. The velocity index is a key factor to decide the heat input during the process. Three samples were manufactured at different velocity index. The hardness measurement was performed to understand the hardness distribution in the processed region at different velocity index. The microstructure examination of the stir zone was performed by optical microscope. All the samples exhibited the stir zone with fine equiaxed grain microstructure. It is observed that grain size decreased with decrease in the value of the velocity index.